Awareness and practices related to dengue fever among rural high school students: a cross sectional study - Ramaiah, Radha; Jayarama, Srividya (International Journal Of Community Medicine And Public Health, 2018)
Background: Dengue is an acute viral infection with potential fatal complications and one of the leading cause of childhood Deaths in our country. Being a major international public health concern, the main method to control or prevent its transmission is to combat vector mosquitoes for which awareness about available preventive methods can play a major role. The objective of the study was to study the awareness and practices of the school students with respect to dengue. Methods: A cross-sectional study was conducted among 369 high school students using pretested structured questionnaire and analysis was done with open Epi and Microsoft excel. Results: The fact that dengue is caused by mosquito bite was known to 96% students respectively. 43% students knew that female mosquito bites and spread diseases. Only 21% knew that they are caused by Aedes mosquito. 47% knew that it breeds in clean stagnant water and 49% knew that it bites during day. Only 50-60% students took personal protective measures against mosquito bites and check for breeding of mosquitoes. 95% students felt that prevention of these diseases should be taught in schools. Conclusions: awareness among students is an important factor for preventing dengue in the community. Findings of the study will be helpful to make strategies for students to enhance knowledge on these diseases. Government should utilize methods of mass communication for educating about mosquito borne diseases.